Doubled plots : romance and history - Strehle, Susan; Carden, Mary Paniccia (University Press of Mississippi, 2003)
"In art, myth, and popular culture, romance is connected with the realm of emotions, private thought, and sentimentality. History, its counterpart, is the seemingly objective compendium of public fact. In theory, the two genres are diametrically opposed, offering widely divergent views of human experience."